Hipoidratação em escolares e sua relação com o consumo de água livre e o estado nutricional - Dias, Francine Canovas [UNIFESP] (2016)
Objectives: To assess the prevalence of hypohydration in students according to urine osmolality; to study the relationship between hypohydration and: free water consumption, nutritional status and seasons; and to evaluate the diagnostic value of the use of a urine color scale to characterize hypohydration in students. Methods: A cross-sectional study conducted at two public schools in the city of Osasco, SP. The evaluation of the state of hydration was carried out according to urinary osmolarity adopting the cutoff of 800 mOsm/kg. Results: A total of 475 students were evaluated, 60.4% (N=287) were female and 39.6% (N=188) were male. The overall prevalence of hypohydration in the studied population according to urine osmolality was of 63.1%, of which 40.8% had intense hypohydration and 22.3% had maximum hypohydration. The frequency of hypohydration was higher in males than in females (p =0,007) and was more frequent in winter than in other seasons (29.9%; p=0,002). There was no correlation between the urine color scale and urine osmolality (Kappa=0,04). Hypohydration showed no relation with socioeconomic status, nutritional status and estimated free water consumption. Conclusion: There was a high prevalence of hypohydration in studied students, being more frequent in males and during winter.